Improving the Diagnosis and Treatment of Thoracoabdominal Injuries - Khojimatov Gulomidin Minhodzhievich; Yahyoyev Sardorbek Mamasobir ugli (Genius Journals, 2023)
A diagnostic and tactical algorithm has been developed to make a timely diagnosis of injuries and choose adequate therapeutic tactics. The important role of endovideosurgical methods in diagnostics and choosing treatment tactics of patients with posttraumatic thoracic and abdominal cavity injuries has been shown. The results of diagnostics and treatment of the patients with the thoracoabdominal injuries were analyzed using the diagnostic and treatment algorithm designed by the authors. The application of the treatment and diagnostic approaches developed by the authors improved the results of treatment of this severe category of patients.
Keywords: traumatic thoracic and abdominal injuries; laparoscopy; thoracoscopy